The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/su13169270
|View full text |Cite
|
Sign up to set email alerts
|

BIMp-Chart—A Global Decision Support System for Measuring BIM Implementation Level in Construction Organizations

Abstract: Building Information Modeling (BIM) is recognized as one of the most significant technological breakthroughs in the Architecture, Engineering, and Construction (AEC) industry. The pace of implementation of BIM in AEC has increased during the past decade with an enhanced focus on sustainable construction. However, BIM implementation lags its potential because of several factors such as readiness issues, lack of previous experience in BIM, and lack of market demand for BIM. To evaluate and solve these issues, un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 76 publications
1
22
0
Order By: Relevance
“…The main idea of this study highlights that the relationship between digital technology and BIM is interrelated [24], [25], [26]. Students from tertiary education institutions need to master both theories and digital skills during their undergraduate study, where BIM is emphasized as part of information technology [3], [7], [27].…”
Section: Introductionmentioning
confidence: 99%
“…The main idea of this study highlights that the relationship between digital technology and BIM is interrelated [24], [25], [26]. Students from tertiary education institutions need to master both theories and digital skills during their undergraduate study, where BIM is emphasized as part of information technology [3], [7], [27].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing research efforts have been devoted to prompt the adoption of BIM such as identifying critical success factors (CSFs) for BIM implementation, developing a framework for implementing BIM, focusing on the benefits, barriers and risks of BIM implementation as well as assessing the level of BIM implementation (Porwal and Hewage, 2013;Won et al, 2013;Miettinen and Paavola, 2014;Bradley et al, 2016;Jung and Lee, 2016;Antwi-Afari et al, 2018;Khoshfetrat et al, 2020;Malik et al, 2021;Othman et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…, 2016; Jung and Lee, 2016; Antwi-Afari et al. , 2018; Khoshfetrat et al , 2020; Malik et al , 2021; Othman et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the authors suggested two scheduling methods for sensor deployment: heuristic and ant colony. The solution to the cover set issue, as stated in the preceding article, is explained in [49][50][51][52]. The authors described the learning automata algorithm in this paper.…”
Section: Related Workmentioning
confidence: 99%